REGULATION OF A BANK’S CREDIT RISK IN THE CONTEXT OF ECONOMIC INSTABILITY: A CASE STUDY OF UKRAINE - Лариса Гриценко; Ірина Кожушко; Онур Ерісен; Віталій Романчукевич; Євген Чернов; Петро Тарабановський (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article is devoted to the issue of regulating the bank's credit risk in the context of economic instability. The relevance of the study is due to the high level of influence of the volatile environment on the credit risk and the efficiency of the bank's functioning. The article is aimed at assessing the mechanisms of state regulation of the bank's credit risk in the context of economic instability in Ukraine's case study. The article considers the requirements of Basel III, which regulates this aspect of banking activity at the European level. In the course of the study of Ukraine's experience, a detailed analysis of the adaptation of international standards to the existing conditions of the national banking system was carried out on the basis of the provisions set out in the Resolution of the National Bank of Ukraine No. 351. In order to assess the impact of adapting Basel III requirements the quality of the loan portfolio of five Ukrainian banks and the banking system as a whole are analyzed. The statistical study established the relationship between the level of credit risk, adequacy of provisions and profitability of banking activities. The results of the assessment demonstrated a significant positive impact of the NBU's approaches on the process of maintaining the stability of the banking system in the current socio-political crisis. The scientific novelty of the work lies in a comprehensive assessment of the effectiveness of credit risk regulation of banks in Ukraine in the context of economic instability, including an analysis of the harmonization of international standards with the national conditions, and an empirical study of the impact of adapted requirements on the quality of the loan portfolio. The study identified prospective directions for improving the methodology for assessing and managing credit risk in the context of economic instability.